2017
DOI: 10.1902/jop.2017.170197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Periodontal Parameters and Self‐Perceived Oral Symptoms Among Cigarette Smokers, Individuals Vaping Electronic Cigarettes, and Never‐Smokers

Abstract: Periodontal inflammation and self-perceived OSs were poorer among CSs than among vaping individuals and NSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
122
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 26 publications
6
122
0
3
Order By: Relevance
“…The findings of the present study show that the levels of soft and hard tissue damaging proinflammatory cytokines (MMP‐9 and IL‐1β) were significantly higher among individuals in CS and vaping individuals compared with NS. One explanation in this regard is that nicotine in tobacco increases the levels of AGEs in oral tissues including gingival and periodontal tissues . Augmented interfaces between AGEs and their receptors (RAGEs) have been associated with the formation of ROS that induce a state of oxidative burst within gingival tissues, reduced chemotactic, and phagocytic function of polymorphonuclear cells, decrease production of antibodies, thereby increasing bacterial adhesion, and systemic and local inflammatory burden through increased expression of cytokines in the serum and crevicular fluid .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the present study show that the levels of soft and hard tissue damaging proinflammatory cytokines (MMP‐9 and IL‐1β) were significantly higher among individuals in CS and vaping individuals compared with NS. One explanation in this regard is that nicotine in tobacco increases the levels of AGEs in oral tissues including gingival and periodontal tissues . Augmented interfaces between AGEs and their receptors (RAGEs) have been associated with the formation of ROS that induce a state of oxidative burst within gingival tissues, reduced chemotactic, and phagocytic function of polymorphonuclear cells, decrease production of antibodies, thereby increasing bacterial adhesion, and systemic and local inflammatory burden through increased expression of cytokines in the serum and crevicular fluid .…”
Section: Discussionmentioning
confidence: 99%
“…reported that e‐cig aerosols with flavoring agents may have a negative impact on oral epithelial cells and gingival fibroblasts through DNA damage and elevated expression of proinflammatory cytokines such as cyclooxygenase (COX)‐2 and prostaglandin E2 (PGE 2 ). Furthermore, a recent cross‐sectional pilot study by Javed et al . demonstrated statistically higher periodontal inflammation among CS and individuals vaping e‐cigs as compared with never smokers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This hypothesis was based results from previous clinical studies in which, oral soft tissue inflammation and alveolar bone loss (ABL) around natural teeth and dental implants was shown to be significantly higher among CS compared with NS. 7,16,19,20 Moreover, tobacco smoking increases the AGES-RAGE interactions thereby increasing the production of destructive inflammatory cytokines, such as IL-6 and IL-1b. 10,11 Increased levels of these cytokines in the oral fluids have been associated with the etiology of periodontal and peri-implant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: We read with interest the pilot study by Javed et al . comparing periodontal parameters in cigarette smokers, electronic cigarette (e‐cigarette) users, and never‐smokers.…”
mentioning
confidence: 99%